PENGEMBANGAN FLIPBOOK BERMUATAN WAYANGSUKURAGA UNTUK MENINGKATKAN KETERAMPILANMEMBACA PEMAHAMAN DAN REGULASI DIRI SISWA KELAS V SEKOLAH DASAR - Fitri Rahmawati; Hilman Hilmawan; Rahmatika Layyinah; Anisya Fitriyani; Sri Lestari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was conducted based on the finding that elementary school students’ reading comprehension and self-regulation skills still need to be improved. In addition, the learning media used in the learning process have not been able to optimally capture students’ attention. This study aims to produce a Wayang Sukuraga-based flipbook suitable for use and to test its effectiveness in improving the reading comprehension and self-regulation skills of fifth-grade elementary school students. This study used the Research and Development (R&D) method with the ADDIE model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The study subjects included 15 students in the small-group pilot test and 67 students in the large-group pilot test. The validation results showed that the developed flipbook received a rating of 83.3% from media experts, 85% from content experts, 76% from language experts, and 80% from self-regulation questionnaire experts, with ratings ranging from “acceptable” to “highly suitable.” The results of the media implementation showed an improvement in students’ reading comprehension skills. In the small-group pilot study, the average pretest score of 60.5 increased to 81.4 on the posttest. Meanwhile, in the large-group pilot study, the average pretest score of 54 increased to 83 on the posttest. The results of the hypothesis testing yielded a significance value of 0.000 (Sig. < 0.05), indicating that the use of a flipbook featuring Wayang Sukuraga had a significant effect on improving students’ reading comprehension skills. Furthermore, the use of this educational medium also supported the development of students’ self-regulation in the areas of metacognition, motivation, and learning behavior.